Teaching our Ways of Knowing: A Cultural Imperative for Integrating Indigenous Languages in Zimbabwe’s School Curriculum - Moyo, Mthokozisi (Midlands State University Press and Publications, 2022)
Until 2013, indigenous languages (except Shona and Ndebele) have been given very little vitality in education and the knowledge of these languages has always been ignored even in communities where they are dominant. However, an education that legitimises the cultural norms of only one culture within a pluralistic society robs learners form other cultural backgrounds of their self esteem and the potential of pursuing different careers. The decision to integrate indigenous languages into the education curriculum is a step towards full-blown multiculturalism and linguistic pluralism in the country, creating numerous opportunities for cultural industries and the overall knowledge economy. This diversity in knowledge development dissects the normative monolithic approach to education that alienates and disadvantages some groups of students and their communities. It, therefore, becomes fundamentally important to campaign for an education that recognizes the linguistic potential of students of different cultures; such an education contributes to the knowledge economy underpinned by unique ways of understanding and experiencing the world